CONTENT OF HEAVY METALS IN WILD-GROWING MUSHROOMS IN “DILIJAN” NATIONAL PARK (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
We investigated the concentration of heavy metals in fruit bodies of 7 species (Agaricus bisporus (J.E. Lange) Imbach, Armillaria mellea (Vahl) P. Kumm., Chroogomphus rutilus (Schaeff.: Fr.) O.K. Mill., Hypholoma fasciculare (Huds.: Fr.) P.Kumm., H. sublateritium (Fr.) Quél., Phallus impudicus (L.: Pers.), Pleurotus pulmonaris (Fr.: Fr.) Quél.) of wild-growing mushrooms in “Dilijan” National Park. The data indicated high concentration of metals (Cu, Zn, Pb, Cd, Co, Ni, Fe, Mn) in the fruit bodies. From the toxicological point of view it is important to note the high concentration of Cd and Pb, on average 15.1 and 23.6 μg/g, respectively. Periodic use of studied edible mushrooms in food can cause intoxication.
Keywords: concentration of heavy metals; fruit bodies; edible mushrooms; intoxication